Presentation - Marcos Antonio Alves; Zhenling Liu (Trans/Form/Ação, 2022)
Traditional Chinese philosophy sprouted from the religious thought of the Yin or Zhou Dynasty, and reached its first peak in the Warring States (Zhan Guo) period of ancient China. It is considered to be the contentious period of a hundred schools of thought. Daoism and Confucianism developed during this time of intense warfare. We could say that scholarship was developing from a state of chaos to refinement. Since then, Chinese philosophy has undergone several major changes in the Wei, Jin, Tang, Song, Ming and Qing Dynasties, blending Confucianism, Buddhism, and Daoism, evolving into many diverse schools of thought such as Song and Ming Neo-Confucianism, especially Zhu Xi’s and Wang Yangming’s interpretations. Their influence has radiated throughout East Asia and the world.